Difficulties and Proposed Solutions in Translating Cultural-Bound Expressions from English into Arabic - Hmaidan , Marvet Abed Ahmad (Journal of Ecohumanism, 2024)
Arabic and English are two distant languages in terms of origin, culture, religion, customs, history, and beliefs and this is apparent through the nature of their cultural expressions which makes each language distinctive and peculiar. When it comes to compare between them, the differences far outweigh the similarities as they originated from different parts of the world. Understanding the nature of cultural translation helps interacting with others, who are different to overcome social, ideological, and political problems. The main difficulty in translating cultural expressions lies in their figurative nature, as they are culture-bound expressions and carry an implicit meaning which goes beyond their literal meaning. Hence, this study aims to investigate the difficulties of translating English cultural-bound expressions into Arabic among Jordanian universities undergraduates majoring in translation, and also to propose solutions to overcome these difficulties. In this descriptive case study, data were collected using a qualitative approach. Twenty students were recruited in the present study in semi-structured interviews as participants using a purposive sampling method. The participants’ responses were analyzed using a thematic analysis. The study revealed five themes that reflect numerous difficulties encountered in translating cultural-bound expressions, which are ability to recognize the expression itself, culture-bound nature of them, ambiguity, lack of equivalence, and lack of knowledge of translation strategies. Also, four themes were emerged as proposed solutions, which were raising students’ awareness of cultural expressions, motivating students to use them in their daily life, using authentic materials to learn them, and incorporating such expressions in the curriculum. The study is significant in raising students’ awareness of the difficulties encountered in translating cultural-bound expressions and proposed solutions for future translation works. The study has implications on instructors and translators to give emphasis on the language and cultural perspectives in executing translation processes.